A pulmonary arteriovenous malformation treated with percutaneous intervention - Ahmet Tütüncü; Hasan Arı; Sencer Çamcı; Selma Arı; Tahsin Bozat (KARE Publishing, 2019)
A pulmonary arteriovenous malformation (PAVM) is a rare anomaly that may have significant clinical complications. PAVMs are commonly seen in patients with hereditary hemorrhagic telangiectasia, while some 10% of PAVMs may be idiopathic. PAVMs can cause cyanosis, fatigue, polycythemia, and paradoxical thromboembolic complications. The diagnosis and treatment of a PAVM should be performed with great care, as the disorder may be fatal if not properly treated. Percutaneous closure (such as embolization) can be very beneficial. Presently described is the case of a 23-year-old man with an idiopathic PAVM who was treated percutaneously with 3 vascular plugs.